Kurdish women fighters of Rojava: The rugged pathway to bring liberation from mountains to women’s houses - Ζαγορίτου, Αικατερίνη (Πανεπιστήμιο Πελοποννήσου, 2019)
Kurdish women fighters of YPJ units in the de-facto autonomous region in Northern Syria, mostly known as Rojava, have become prominent in the West during the liberation of Kobanî in early 2015. Most attention has been paid to their struggle against ISIS, whilst their historical background has been often neglected and their feminist struggle has been understated. The aim of this MA Thesis is to delve into the relationship between the participation of Rojavan female fighters in the armed struggle and their further empowerment and emancipation. The examination of the history of the Kurdish women’s liberation movement, as well as of the ideological framework within which their struggle takes place will contribute to better understand this relationship. Furthermore, we argue that the participation of Rojavan women in armed struggle is differentiated from similar female armed movements which experienced backlashes in a post-conflict/liberation period, due to its historical context and ideological framework, alongside the fact that women’s active participation is currently fostered and their emancipation is taking institutional forms implemented at present instead of being postponed to an uncertain and remote future if and when the prioritized goal will have been achieved.
Κούρδισσες γυναίκες μαχήτριες της Ροζάβα: Το δύσβατο μονοπάτι για την απελευθέρωση από τα βουνά στα σπίτια των γυναικών
Syria
Keywords: Women; Feminism; Violence; War; Northern Syria; Rojava; Kurdish women fighters; Liberation; Gender